Evaluation of Meningococcal Serogroup C Bactericidal Antibodies after Primary Vaccination: A Multicentre Study, Italy - Arianna Neri; Massimo Fabiani; Anna Maria Barbui; Caterina Vocale; Alessandro Miglietta; Cecilia Fazio; Anna Carannante; Annapina Palmieri; Paola Vacca; Luigina Ambrosio; Paola Stefanelli (Vaccines, 2022)
Here, we evaluated over time in different cohorts of children vaccinated against serogroup C Neisseria meningitidis, the presence of antibodies with neutralizing activity. A total of 348 sera samples of enrolled children by year since vaccination (<1 year- up to 5 years), starting from February 2016 to December 2017, were collected in three collaborating centers. Meningococcal serogroup C (MenC) antibody titers were measured with a serum bactericidal antibody (SBA) assay using rabbit complement (rSBA) following standard operating procedures. The cut-off of rSBA titer ≥ 8 is considered the correlate of protection. We observed a significantly declining of bactericidal rSBA titers by 23% every year, for every 1-year from vaccination (Adjusted PR = 0.77, 95% CI: 0.71–0.84). The proportions of children with bactericidal antibodies, immunized with the meningococcal serogroup C conjugate (MCC) vaccine, declined from 67.7% (95% CI: 48.6–83.3%) one year after vaccination, to 36.7% (95% CI: 19.9–56.1%) five years after vaccination (chi-square for linear trend, p < 0.001). Children vaccinated with the tetravalent meningococcal serogroup ACWY vaccine resulted in a high proportion of bactericidal rSBA MenC titer ≥ 1:8 (90.6%, 95% CI: 79.3–96.9%) after a mean time of seven months. Overall, the results provide some evidences on the evaluation of meningococcal serogroup C bactericidal antibodies after primary vaccination.